(untitled) (PANGEEA, 2025)
Sebes city and environmental issues. Sebes is an ancient medieval burg, founded in 12th century, by Saxon settlers. A continuously evolved and is today a city with high literacy and significant savings. Environmental problems of the municipality are caused by the activity of Kronospan company that processes wood. In the industrial process passes into the atmosphere large amounts of harmful gases (formaldehyde) and wood dust. They produce the pollution of main components of environmental: the atmosphere, surface waters and groundwater, soils and vegetation and has harmful effects on health.